Trastorno por Déficit de Atención/Hiperactividad (TDAH) y dificultades en lenguaje pragmático (2014)
ABSTRACT: This paper emphasizes the pragmatic dimension of language in children diagnosed with attention deficit hyperactivitydisorder. First, an analysis of variations in the prevalence of this disorder in Colombiait is done taking into account language and cognition features, and behavioral assessment as well. Later, it is laid emphasis on studies from neurocognition and the connecting links found between language problems and brain’s executive function changes related to this disorder. The evolutionary profile of adhd, the way how the pragmatics of language has been studied, and interest in the impact of these changescancausein the children social life with adhd are showed.